Forward Kinematics Analysis of 3-RRRS Mechanism with Redundant Drive Characteristic - Zhang Yuhui; Yang Xu; Wang Liangwen; Song Kangkang (Jixie chuandong)
The 3- RRRS mechanism is adopted to connect motion platform with static platform,which can achieve the 6 dimensions change of pose for static platform relative to moving platform. Releasing S vice,the mechanism configuration can be used for the general structure of reptiles bionic robot. Because the mechanism configuration has redundant drive characteristics,it can improve motion performance and work space of motion platform. The forward kinematics problem is studied. Firstly,according to the structure relationship,the motion equations including redundant drive variables are established. Secondly,the redundancy drive variables are solved by Bezout equation and variable substitution. Finally,a calculation model of the motion trajectory and direction matrix for motion platform are obtained. An analysis example is described. A reference for solving the similar problem is provided.